Legality of Agricultural Products Weight Cutting as a Cost of Risk in Trade - Farida Arianti; Pauzi M; Abdul Mughits; Ridwan Nurdin; Abdo Yousef Qaid Saad (JURIS (Jurnal Ilmiah Syariah), 2023)
Agricultural goods transactions with toke (in Bahasa is known as a traditional market agent) always carry a weight cutting of one to 2 kilograms per bag. Risk reduction is considered a burden to be borne. Therefore, how to study the law in the aspect of risk imposition when transactions occur between plantation farmers and toke in traditional markets. The aim of this research was to examine how weighing is carried out and the recognition of the weight of agricultural products on scales is associated with possible risks that will occur in the future. This research method was qualitative, field research. Data sources were garden sellers/farmers and toke in traditional markets. Data collection through interviews and examination of artifacts. Data analysis technique was qualitative descriptive. The research finding showed that when the agricultural harvest was sold, there was a scale cut of around 2 kg per bag, such as chilies, ginger, corn and so on. The result of reducing the scale in dealing with the risks that will occur with irregular goods. The risk was borne by the farmer/seller, this was suspected and endangers the continuity of the relationship between farmer, toke, retailer towards objects that change naturally. Cutting the weight of the scales was still permitted as long as it was within appropriate limits. Recommendations for cutting the weight of the scales when changing goods and not fixed goods.